The School Literacy Movement at SDIT Nurul Yaqin Jakarta - Dewi Indah Susanti; Ila Nafilah; Mildan Arsdan Fidinillah (Scope : Journal of English Language Teaching, 2022)
The School Literacy Movement (GLS) is an implementation of the Regulation of the Minister of Education and Culture Number 23 of 2015 concerning on the “Cultivation of Character”. Literacy culture is a habit of thinking followed by a reading-writing process which will eventually lead to critical thinking, problem solving, scientific development, and creation of works. This study aims to describe the policy of the school literacy movement at SDIT Nurul Yaqin. This type of study was a qualitative descriptive study with a case study approach. Data collection techniques employed interviews, observation and documentation. Source triangulation was conducted to ensure data validity. Research results point out as: (1) programs that support the GLS policy at SDIT Nurul Yaqin comprise of reading times, exhibitions, reading corners, story-telling, wall magazine, numeracy literacy, and making comics; and (2) factors supporting the implementation of the GLS policy program at SDIT Nurul Yaqin include commitment of the principal, participation of parents, support from the school community, allocation of 15 minutes of time for literacy, and varied media literacy. The inhibiting factors for GLS at SDIT Nurul Yaqin include inadequate books, inadequate library space, no GLS bureaucratic structure, and students’ reading awareness is still low